PERFORMANCE OF THREE ARMS SIGNALIZED INTERSECTION AT SALABENDA IN BOGOR REGENCY - Syaiful, Syaiful; Siregar, Hermanto; Rustiadi, Ernan; Hariyadi, Eri Susanto (ASTONJADRO, 2022)
The increase in urban transportation in the 2000s era was very high. The use of motorized vehicles during the pandemic has decreased slightly with the government's ban on traveling out of town, including the 2020 homecoming and 2021 homecoming. Most people who travel are in the city center, including the city of Bogor and Bogor district. The travel patterns are very diverse, but most use public transportation and private transportation in addition to freight transportation with a fairly high intensity, especially at night. The purpose of this study was to obtain the LoS value at the signalized intersection of the three arms of the Salabenda intersection. The three-arm Salabenda intersection is the border between Bogor regency and the city of Bogor, so this intersection is one of the busiest and most densely populated intersections beside the Ciawi intersection in the north. The Salabenda intersection has become more congested with the opening of the Section IIIA Toll Road so that the traffic load shifts from Jl. KH. Sholeh Iskandar to this toll road, so that the intersection will have a higher traffic intensity. From the three observations and data collection in the field, it can be seen that in the afternoon it has a very high LoS, namely E. Followed by a LoS D level in the afternoon and in the morning LoS is still in the form of C. So it is still safe to use in the morning with a recommended level. The LoS E condition is a condition where the intersection has a degree of saturation of 0.926, which is almost close to 1, exacerbated by high side resistance activity.